(untitled) (Jurnal Tahsinia, 2025)
The writer carried out this research paper to find out whether an influence of study teaching was listening who are taught by using song and storytelling. Based on the objectives of the study the writer used comparative study. The population in this research was the tenth-grade students of SMPN 2 Pamarayan The number of populations at the tenth-grade students of SMPN 2 Pamarayan are 125 students from three classes: 40 students VIII A 40. The writer took one class of 40 students at class VIII A 40 as the sample. In this research, the writer used comparative data. Then the writer used t-test and correlation coefficient from the instrument of song mastery, it is obtained that the highest score is 8 and the lowest score is 5. The mean (the average score) is 6, 3. Meanwhile, form the instrument of storytelling mastery, it is obtained that the highest score is 9 and the lowest score is 6. The mean (the average score) is 7.3. The data and calculation are presented in appendix 2. The statistic computation using t-test formula shows that the result of standard deviation is 3.42 and the standard error of differences between two means is 0.54, the result of to is -1.83. The value of ttable based on the degree of freedom (df) 39 at 0.05 significant level is 2.045, it shows that to is higher than ttable (1.85>2,02). So it means that to is significant. The statistic computation using correlation shows that the coefficients of correlation (ro) between song and storytelling are 9.281. The value of rtable at 0.05 significant level for N=40 is 9.281. it shows that ro is significant. The calculation is that there is a positive and significant correlation between Song(X) and Storytelling(Y). The computation can be seen in appendix 3.